The impact of cattle grazing and treading on soil properties and the transport of phosphorus, sediment and E. coli in surface runoff from grazed pasture. Issue 6 (2nd November 2022) - Gray, Colin W.; Ghimire, Chandra P.; McDowell, Richard W.; Muirhead, Richard W.
ABSTRACT: Contaminant loss from grazed pasture can negatively affect freshwater quality. There is, however, little data on the impact of different levels of grazing/treading on contaminant loss measured under field conditions. This study quantified phosphorus (P), sediment and Escherichia coli ( E. coli ) loss in surface runoff from plots grazed by cattle for 0, 16 or 28 h to create different pasture/treading damage. Results showed an increase in grazing/treading duration decreased soil macroporosity (30%) and saturated hydraulic conductivity (96%), and increased surface roughness (71%) and depression water storage capacity (388%). These changes in soil physical condition contributed to greater volumes of surface runoff in the 16 h (31%) and 28 h (55%) treatments. Contaminant concentrations and loads in runoff also tended to increase with grazing/treading, although the increases were not statistically significant. An exception was total P (TP) which increased from 0.323 to 1.222 kg ha −1, principally due to increased dissolved P, probably released from plants due to grazing and from the deposition of dung. Management of animals to minimise the number, duration and frequency of grazing wet soils that are vulnerable to physical damage are likely key factors to reducing TP, and probably SS and E. coli transport in surface runoff.